The effect of giving bitter leaf (Vernonia Amygdalina) flour in ration on the hematological profiles in laying hens rejection phase - Firdaus, Rizal Faturrohman; Latipudin, Diding; Rusmana, Denny; Harahap, Rakhmad Perkasa (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This study aimed to determine the effect of bitter leaf flour in ration with different levels of laying hens on the haematological profile. The materials used were 20 laying hens with Hy-line strain, 110 weeks old, placed in battery cages and feed with 16-18% crude protein content of 120 grams/head/day and drinking water addlibitum. Methods: The research was conducted using an experimental method with a completely randomized design four treatments that were repeated five times. The treatments were given in the form of bitter leaf flour in ration with levels of P0: 0% (control), P1: 1%, P2: 2%, P3: 3%. The variables measured were haematological profiles such as erythrocytes, haemoglobin, hematocrit and leukocytes. The data obtained were then analyzed using analysis of variance. Finding: The results showed that giving bitter leaf flour in ration with levels of 0%, 1%, 2%, and 3% had no significant effect (P>0.05) on erythrocytes, hemoglobin, hematocrit, and leukocytes of laying hens. Connclusion: It was concluded that giving levels of bitter leaf flour up to 3% did not affect the haematological profile of laying hens. Novelty/Originality of this Article: The novelty of this study lies in its exploration of bitter leaf flour (Vernonia Amygdalina) as a natural feed additive in the diet of elderly laying hens (110 weeks old), a topic that is still underrepresented in poultry research, especially regarding its effect on haematological health parameter.